Commissioning of pencil beam and Monte Carlo dose engines for non-isocentric treatments in scanned proton beam therapy. (28th August 2019) - Carlino, A; Böhlen, T; Vatnitsky, S; Grevillot, L; Osorio, J; Dreindl, R; Palmans, H; Stock, M; Kragl, G
Abstract: This work describes the dosimetric commissioning of the treatment planning system (TPS) RayStation v6.1 from RaySearch Laboratories (Stockholm, Sweden) for a synchrotron-based scanned proton beam delivery with isocentric and non-isocentric setups at MedAustron. Focus was on the comparison of the pencil beam (PBv4.1) and Monte Carlo (MCv4.0) calculation algorithms. Commissioning of dose calculations was done first for 1D/2D dose delivery where the performance of the beam model in reproducing dosimetric properties for the delivery of single static pencil beams and mono-energetic layers with multiple spots was evaluated. The commissioning for 3D beam delivery employed test cases with increasing complexity: from box-shaped fields in homogeneous phantoms to the introduction of oblique incidences and inhomogeneities. Dose calculations were compared to the measured data for different air gaps and using beams with and without range shifter (RaShi). Depth-dose curves and spot shape comparisons showed good agreement of the results obtained with PBv4.1 and MCv4.0 algorithms at isocentric setup for open beam configurations (without RaShi). Comparison of transverse dose profiles for lateral heterogeneities at different depths showed better performance of the MCv4.0 algorithm in comparison to the PBv4.1 algorithm. In the case of 3D delivery comparisons of measured and TPS-calculated dose with MCv4.0 algorithm in box-shaped fields in water showed an average agreement within 2%. The results for dose calculations with the PBv4.1 algorithm showed larger deviations for beams with RaShi at all evaluated air gaps (from 64.8 cm to 14.8 cm). Our results suggest that the MCv4.0 algorithm shall be used in clinics for final dose calculation when beams with RaShi are used especially in the presence of large air gaps, inclined patient surface and lateral inhomogeneities. The detailed stepwise methodology implemented for the RayStation commissioning in this work could serve as further guidance for other facilities introducing a new TPS for proton beam therapy.